Formy współpracy administracji publicznej z organizacjami pozarządowymi : na przykładzie stowarzyszeń i fundacji - Pleśniak, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article describes relations and forms of cooperation between public administration bodies, both government and local government administration, and non-governmental organizations (NGOs) belonging to the so-called “Third sector”. Associations and foundations are the most popular forms of NGOs. The basis for their functioning are the Constitution of the Republic of Poland, which guarantees freedom of association and foundation, and relevant acts, i.e. Law of Foundations and Law of Associations. There is no single, closed definition of the terms: public administration and administrative body. In literature they are defined by an indication of their characteristic features. We distinguish two forms of cooperation between the third sector and public administration: financial and non-financial. Financial support forms include targeted donations to NGO’s public tasks, financial guarantees, loans and sureties given to perform public service tasks. The range of non-financial forms of cooperation includes among others consultations with non-governmental organizations on formulating legal acts related to their statutory activities, the establishment of joint advisory boards, the creation of units supporting the activities of third sector organizations, or the transfer of real estate to be used by non-governmental organizations
Keywords: administracja publiczna; organizacje pozarządowe (NGO); współdziałanie; województwo dolnośląskie